A Survey on Stable and Efficient Data Dissemination clustering algorithms for VANETs - Hande, Rajendra S; Muddana, Akkalakshmi (International Journal of Computer Sciences and Engineering, 2019)
Vehicle Ad-hoc Network (VANET) is an emerging technology that ensures road safety by enabling wireless communications. VANETs have drawn greater attention due to their significant attractive features such as dynamic connectivity, self-management and no centralized administration. However, due to the high mobility and the large scale of the network lead to dynamic topology. The rapid and continuous changing topology causes frequent disconnections of the communication links, which results in an increased overhead of the communication protocols. To resolve such problems, many of the clustering algorithms have been proposed for providing an efficient communication among vehicles. In this paper, we are most concerned about to explore the different clustering algorithms for improving routing stability and reliability even with dynamic mobility and dynamic topology.